Bioinsecticidal Activities of Azadirachta indica A. Juss (Meliaceae) Seed Oil Extracts on Sitophilus zeamais Motschulsky, 1855 (Coleoptera: Curculionidae) on Stored Maize - Michael, Obembe Olusola; Tejumade, Philip-Attah Mary; Temitope, Omotoso Olumuyiwa (Darul Yasin Al Sys, 2025)
The preservation of stored grains against weevil infestations is critical for ensuring food security and minimizing post-harvest losses in Nigeria, where insect pests remain a major constraint to effective grain storage. This study evaluates the efficacy of seed extracts of Azadirachta indica in controlling Sitophilus zeamais. Seeds were extracted using five solvents—methanol, ethanol, acetone, petroleum ether, and n-hexane—and the resulting oils were tested for their effects on insect mortality, oviposition, adult emergence, grain damage, and long-term storage viability. Results indicate that ethanol extract was the most effective, inducing 100% mortality within 96 hours of exposure, followed by n-hexane (88.25%), petroleum ether (85.75%), methanol (82.25%), and acetone (76.15%). Extracts also significantly reduced oviposition and adult emergence, with complete suppression observed in ethanol-, petroleum ether-, and n-hexane-treated grains. These treatments also fully prevented grain damage and weight loss for three months, while methanol and acetone extracts allowed limited damage (9.19% and 8.18%, respectively). Germination tests showed high viability (95.25–98.25%) across all treatments, with the lowest germination recorded in petroleum ether extract (95.25%). The findings suggest that A. indica seed extracts are highly effective in managing S. zeamais infestations and represent a viable alternative to synthetic insecticides for safe and sustainable grain storage.